Comparative advantage, multi-product firms and trade liberalisation: An empirical test - Catherine Fuss; Linke Zhu (National Bank of Belgium, 2012)
This paper investigates how economies of scope in multi-product firms interact with comparative advantage in determining the effect of trade liberalisation on resource reallocation, using Belgian manufacturing firm- and firm-product-level data over the period 1997-2007. We first provide evidence on industry integration induced by multi-product firms producing simultaneously in multiple industries and on the extent to which industry integration occurs between industries that have different degrees of comparative advantage. We then examine the impact of opening up trade with low-wage countries on both inter- and intra-industry resource reallocation, taking into account heterogeneity in the integration rate across sectors and industries. Our results indicate that, within more closely integrated sectors, trade liberalisation with low-wage countries leads to less reallocation from low-skill-intensity (comparative-disadvantage) industries to high-skill-intensity (comparative-advantage) industries, both in terms of employment and output. We also find that more integrated industries experience less skill upgrading after trade liberalisation with low-wage countries. Furthermore, we find that within sectors with a low integration rate, trade liberalisation with low-wage countries induces relatively more aggregate TFP and average firm output growth in comparative-advantage industries than in comparative-disadvantage industries, in line with the prediction of Bernard, Redding and Schott (2007), while the opposite is true in highly integrated sectors. Decomposition of the industry-level aggregate TFP changes reveals that the result is mainly driven by reallocation between incumbent firms within industries. Overall, the results are highly consistent with the predictions of the Song and Zhu (2010) model.
Keywords: F11; F12; F14; L23; 330; trade liberalisation; industry integration; comparative advantage; firm heterogeneity; microeconomic panel data; Total Factor Productivity; Mehrproduktfertigung; Handelsliberalisierung; Komparativer Vorteil; Panel; Produktivität; Mikroökonomik